Molecular evidence for taxonomic status of the gudgeon genus Huigobio Fang, 1938 (Teleostei: Cypriniformes), with a description of a new species from Guangdong Province, South China - Jiang, Zhong-Guan; Zhang, E. (Zootaxa, 2013)
The gudgeon cyprinid genus Huigobio Fang, 1938 is re-diagnosed. It can be distinguished from all other genera of Armatogobionina Kryzhanovsky, 1947 and the Gobioninae by its uniquely modified lower lip. The lower lip has a small, heart-shaped, longitudinally non-bisected central pad and two lateral lobes expanded as a wing-shaped flap completely covered with papillae. The lobes contact each other posteromedially, but are not completely confluent. Huigobio exilicauda, new species, is described from the Zhu-Jiang drainage of Guangdong Province, South China. It differs from H. chenhsienensis in caudal-peduncle thickness and interorbital width.